PELATIHAN BEAUTY SHOT PHOTOGRAPHY DENGAN KAMERA HANDPHONE PADA MURID TATARIAS PENGANTIN DI LKP LELLY MEDAN MARELAN - Desipriani Desipriani; Suprianingsih, M. Fahzurrahman (JOURNAL OF COMMUNITY DEDICATION, 2022)
Beauty-shot is one of the specifications of the world of photography. Beauty-shot is photography which means that everything that is produced in photography should look beautiful, attractive, and bring out the aura of the photo. So the main task of a photographer is no longer about lighting techniques, but the ability to study and explore the character and facial anatomy of the model to be photographed. photography is a combination of the words photos which means light and grapho which means writing, so it can be interpreted that photography is the process of writing or painting using light media. Meanwhile, the Big Indonesian Dictionary (KBBI) explains that the notion of photography is art and the result of the process of light and images on the surface of a film or surface that is made sensitive.